Element‐ and Site‐Specific Many‐Body Interactions in Few‐Layer MoS2 During X‐Ray Absorption Processes. Issue 2 (18th December 2018) - Kamada, Gen; Venugopal, Gunasekaran; Kotsugi, Masato; Ohkochi, Takuo; Suemitsu, Maki; Fukidome, Hirokazu
Abstract : Few‐layer MoS2 is a promising 2D material for nano‐electronic device applications. However, the performance of these devices is often deteriorated. One of the reasons is that the electronic properties are influential to the many‐body effects such as excitonic effects and Anderson orthogonality catastrophe (AOC) which could renormalize the band‐dispersion and density‐of‐states(DOS). Hence, the authors investigate the effect of many‐body interactions on MoS2 device performance by using X‐ray absorption spectro‐microscopy (µ‐XAS) on a few‐layer MoS2 transistor in operation, through the application of gate‐bias or contact with a metal. The results show a significant peak shift in µ‐XAS spectra while varying the gate‐bias. The applied negative gate‐bias induces more holes which attracts excited electrons resulting strong many‐body interactions followed by Fermi level shift. This effect is discussed with the aid of XAS‐Auger electron phenomena. However, the AOC contribution in XAS peak‐intensity is ignored since the bands around the energy‐gap in MoS2 are relatively flat and the DOS is empty above Fermi level (unlike graphene). The authors observe a redshift in photon energy near the MoS2 /metal‐electrode interface due to charge transfer ensuring carrier‐doping induced through metal‐contact. These observations provide significant insight into element‐ and site‐specific many‐body interactions in MoS2 tunable by gate‐bias or contact with a metal. Abstract : This paper demonstrates an element‐ and site‐specific tunability of many‐body interactions in few‐layer MoS2 transistor in operation (in‐situ measurements) by using X‐ray absorption spectro‐microscopy. The author's observation clearly reveals the scientific insights of many‐body interactions in MoS2 tunable by gate‐bias or contact with a metal, which can be very useful in designing new strategies in modern electronic device application.